Implementasi Model Aktualisasi Kegiatan Kepramukaan Kurikulum 2013 Dalam Penanaman Karakter Disiplin Dan Kerja Sama Antar Siswa Pada Gugus Depan Yang Berpangkalan Di SMA Negeri 2 Sukoharjo Tahun Ajaran 2015/2016 - Widayat, Rudi, Drs. Suyahman, M.Si, MH (2016)
IMPLEMENTATION MODEL ACTUALIZATION scouting activities CURRICULUM 2013 IN CHARACTER DISCIPLINE AND INVESTMENT COOPERATION AMONG STUDENTS IN FORCE FRONT-based SMA 2 Sukoharjo STATE ACADEMIC YEAR 2015/2016 Thesis. The Faculty of Education, University of Muhammadiyah Suakarta. August, 2016. This study aimed to describe 1) the implementation of the model actualization scouting activities curriculum 2013 of planting code of discipline and cooperation among students in SMANegeri 2 Sukoharjo, 2) constraints yng faced model implementation actualization scouting activities curriculum 2013 of planting code of discipline and cooperation among students in SMANegeri 2 Sukoharjo 3) solution to the constraints in the implementation of the model curriculum actualization scouting activities in 2013 on the planting of character discipline and cooperation among students in SMANegeri 2 Sukoharjo. This research is a qualitative research. This research data is gathered through informants, places and events, as well as documents. Data collection techniques using the method of observation, interviews, documentation. Analysis of data using interactive model that has multiple stages of data collection, data reduction, and conclusion. Validity of the data using a triangulation of data sources and data collection. The results obtained are: 1) implementation of the model of actualization of scouting activities curriculum in 2013 in the planting of character discipline and cooperation among students at SMA Negeri 2 Sukoharjo is a) familiarize be present on time, b) conduct operations order that the students get used to comply with the rules, c) use uniform in accordance with the provisions, d) the return of the tools and materials in accordance with the place, e) help other members of the group, f) to exchange opinions among members of the group, g) respect the opinions of others, h) the scheduling of tasks and required, i) participate and is present in the current group and scouting activities take place, j) complete a task that has become its responsibilities, k) liveliness to berartisipasi in the group and l) provide a time limit the collection of duties. Constraints model implementation actualization scouting activities curriculum 2013 of planting code of discipline and cooperation among students in SMANegeri 2 Sukoharjo is a) the distance and means of transport, b) lack of awareness of learners, c) the lack of storage equipment and materials, d) the existence of gender differences and the character of the students in the group, e) the existence of selfishness students in the group, f) prohibition and concerns of parents for fear that if children's participation decreased, g) the lack of confidence of students and h) lack of responsibility and concern for scouting duties. Solutions to the problems in the implementation of the model actualization scouting activities curriculum 2013 of planting code of discipline and cooperation among students in SMANegeri 2 Sukoharjo is a) changes in the schedule of activities of scouting, b) regulatory tasks regarding assessment scouting activities, c) use another room to manampung tools and material, d) the rotation and the rotation of members of the group, e) provide motivation to be concerned with the interests of the group, f) give confidence back to the parents to a meeting, g) providing motivation to the group that lacks confidence, h) grant an extension or grace period collection tasks. Keywords: Discipline, Teamwork, Scouting